PENYUSUNAN UNDANG-UNDANG BURUH ANAK DI HINDIA BELANDA MASA KOLONIAL - Darmarastri, Hayu Adi (Patra Widya: Seri Penerbitan Penelitian Sejarah dan Budaya., 2019)
This article examines the attitude of the Dutch Colonial Government toward the existence of child labor as seen from the formation of child labor laws in Netherlands-Indies during the colonial period. The increasing number of plantation companies in the Netherlands-Indies in 1870 had an impact on increasing the need of labor. Apparently not only adults who became workers but children also involved in becoming laborers on plantations. The question raised in this article are how is the role of the Dutch Colonial Government in the process of drafting child labor laws in the colonial period? Are these laws able to eliminate the participation of children as worker in colonial period? This article used the critical historical method. The results of this research indicated that the establishment of a child labor laws was not based on the government’s desire to defend the interests of children as laborers but rather as giving legitimacy to children of a certain age as a legal workers.